Limitations and Opportunities of Child Participation in Climate Change Litigation in Africa. - Mauluka, Gift (Pretoria Student Law Review, 2024)
Climate change legal frameworks call upon countries to mitigate and adapt to the adverse effects of climate change. These frameworks have influenced the creation of policies and laws addressing climate change across the globe. Activists, individuals, and civil society organisations have utilised campaigns, demonstrations, and climate change litigation to compel countries to adhere to their climate change obligations provided in these frameworks. However, climate change litigation is still in its infancy and progressing slowly in African countries. Additionally, children’s involvement in such litigation is limited despite international and domestic legal frameworks permitting their participation. This article argues that children’s participation in climate change litigation in African countries is currently tokenistic and does not afford them meaningful involvement in the decision-making processes in climate change matters. Having presented the importance of child participation, it examines the opportunities and limitations of children’s participation in climate change litigation.
Keywords: Climate Change; litigation; child participation; child rights